Heart Rate–Dependent Hysteresis of T‐Wave Alternans in Primary Prevention ICD Patients. Issue 5 (16th December 2015) - Burattini, Laura; Man, Sumche; Fioretti, Sandro; Di Nardo, Francesco; Swenne, Cees A.
Abstract : Background: T‐wave alternans (TWA) is usually performed at accelerated heart rates (HR) during exercise, while recovery TWA is typically not analyzed. Consequently, it is still unknown if TWA shows a HR‐dependent hysteresis or not. Thus, the aim of the present study was to investigate TWA dependency on HR during both the exercise and recovery phases of an ergometer test, and to evaluate if recovery TWA may contribute to identify subjects at increased risk of arrhythmic events. Methods: Our HR adaptive match filter was used to identify TWA from electrocardiographic recordings acquired during a bicycle ergometer test in 266 patients with implanted cardio‐defibrillator. During the 4‐year follow‐up, 76 patients developed tachycardia or ventricular fibrillation (ICD_Cases) and 190 did not (ICD_Controls). Results: TWA was statistically lower during exercise than recovery for HRs between 75 and 110 bpm (16–21 μV vs 20–27 μV; P < 0.05), and reverse for HRs between 120 and 130 bpm (41–51 μV vs 28 μV; P < 0.05). ICD_Cases and ICD_Controls showed significantly different TWA at 80 bpm (20 μV vs 15 μV; P < 0.05) and 140 bpm (15 μV vs 22 μV; P < 0.05) during exercise, and at 90 bpm (38 μV vs 21 μV; P < 0.05) and 95 bpm (33–24 μV vs 28 μV; P < 0.05) during recovery. Conclusions: TWA shows a HR‐dependent hysteresis and there is a different behavior of TWA in ICD_Cases and ICD_Controls groups. Consequently, beside exercise TWA also recovery TWA may contribute to identify subjects at increased risk of arrhythmic events.